PENGARUH INTERPERSONAL TRUST, KOMPETENSI, INDEPENDENSI, DAN ETIKA TERHADAP SKEPTISME PROFESIONAL AUDITOR - Sari, Ayu Putri Mustika; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research discusses about the influence of Interpersonal Trust, competency, independency, and ethic tothe Skeptiscs of professional auditors. It has been found from the result of analysis that i.e.: (1) interpersonaltrust has significant influence to the sceptics of professional auditors. When the level of interpersonal trustwhich is owned by the auditor is getting better, the sceptics of professional auditor will be better as well; (2)competency has significant influece to the skeptics of professional auditor, it means that when the competencylevel which is owned by an auditor is high, the skeptics of professional auditor obtained is high as well; 3)independency has significant influence to the skeptics of professional auditor, it means that when theindependency level which owned by an auditor is high, the skeptics of professional auditor obtained will be highas well; 4) ethic has significant influence to the skeptics of professional auditor. When the etnic which is ownedby an auditor is high, the skeptics of professional auditor obtains will be improved.Keywords: interpersonal trust, competency, independency, ethic, skeptics of profesional auditor